Prosthetic Rehabilitation of Patient with Anterior Segmental Mandibulectomy Using Cast Partial Removable Denture: A Clinical Report - Maharjan, Anil; Joshi, SP; Shrestha, P. (Journal of Nepalese Prosthodontic Society, 2019)
Marginal mandibulectomy involves resection of mandibular body with overlying soft tissues while maintaining inferior cortex of mandible and its continuity. It may lead to numerous problems associated with mastication, speech and deglutition and esthetics. Problems associated with such defect depend upon location and extent of surgical resection. Prosthodontic rehabilitation of such patient poses challenges because of obliterated vestibular depth, inadequate denture bearing areas for support, lesser number of remaining teeth. This article describes rehabilitation of patient who underwent anterior segmental mandibulectomy with cast partial removable denture to replace the missing teeth and maintain esthetics.